EMOTIONAL INTELLIGENCE AMONG SECONDARY SCHOOL TEACHERS IN SENAPATI DISTRICT, MANIPUR - Singh, Irom Premchand; Meitei, Langonjam Chingkheinganba; Devi, K. Rashitombi (International Journal of Research -GRANTHAALAYAH, 2025)
Teachers are the vital organ of the educational system. They play a dynamic role in bringing quality of education as well as development of the society. Teachers play a crucial role in fostering a well-developed society by providing explicit knowledge and guidance. Their behaviour, personality, and emotional management are vital in guiding students towards success. Emotionally intelligent teachers can overcome students' problems and identify strengths and weaknesses, thereby enhancing the teaching-learning process. Therefore, teachers are essential in fostering a well-rounded and emotionally intelligent society. The study focuses on the emotional intelligence of the secondary school teachers in Senapati district of Manipur. The investigators used Emotional Intelligence Scale EIS-HPD (2011) developed by Hyde, Anukool. et al. the objectives of the study are to study the level of emotional intelligence of the secondary school teachers, to study whether there exists significance difference on the emotional intelligence of secondary school teachers with respect to their gender, stream of teaching (arts and science) and difference of teaching experiences. Descriptive method of research was used in the study and the investigators employs stratified random sampling. The sample of the study was 105n (48 male and 57 female). The findings are that there exists an average level of emotional intelligence, there exists no significance difference on the level of emotional intelligence with reference to their gender, stream, and teaching experiences variation.